Physical-chemical quality analysis of Serayu River water, Banjarnegara, Indonesia in different seasons - Purwono Purwono; Ardhi Ristiawan; Annida Unnatiq Ulya; Hashfi Awali Abdul Matin; Bimastiaji Surya Ramadhan (Sustinere: Journal of Environment and Sustainability, 2019)
This article discusses the analysis of the physico-chemical parameters of water in the Serayu River, Banjarnegara, Indonesia during the dry and rainy seasons. The parameters to be measured are heavy metals, alkalinity, pH, temperature, TDS, TSS, and corrosivity. The sampling location is at the mouth of the Serayu River, where Serayu River water is one of the Mrica Reservoir water sources used for hydroelectric power plants. (PLTA). When the samples were taken in the rainy and dry season in 2018. The results showed that in the rainy season, the surface water pH of the Serayu River estuary was 6.61; the TDS was 178 mg/l; the TSS was 62 mg/l; the BOD was 6.66 mg/l; the COD was 33.31 mg/l; and the nitrate was 4.03 mg/l. Meanwhile, in the dry season, the pH was 8.15; the TDS wa 121 mg/l; the TSS was 55 mg/l; the BOD was 6.35 mg/l; the COD was 31.77 mg/l, and the nitrate was 3.08 mg/l. All physical and chemical parameters meet the quality standards required in Indonesian Government Regulation No. 82 of 2001 concerning Management of Water Quality and Class III Water Pollution Control. The surface water of the Serayu River estuary is weak corrosive which means it is safe for hydropower activities. In general, in the rainy season the chemical physics parameters of the Serayu River estuary water level are higher than the rainy season.